Design of modified prefabricated beamless floors for multi-storey residential buildings - Yermolenko, Dmytro; Nyzhnyk, Oleksandr; Tehza, Ivan; Yefimenko, Olena (Academic journal Industrial Machine Building Civil Engineering, 2022)
The article presents an example of the implementation of the structures of the prefabricated beamless floor system using modified reinforced concrete slabs for a multi-story residential building. A comparative analysis of the effectiveness of the proposed prefabricated beamless floor using modified round hollow slabs with a monolithic reinforced concrete floor was performed. The results of the evaluation of the technical and economic efficiency of the presented floor indicate its competitiveness comparing with traditional structures